Conditioned pain modulation is not altered in recreational athletes with Achilles tendinopathy. Issue 1 (6th October 2020) - Mkumbuzi, Nonhlanhla S.; Mafu, Trevor S.; September, Alison V.; Posthumus, Michael; Collins, Malcolm
Abstract : Background: Altered central pain mechanisms is a feature of other chronic pain states and upper limb tendinopathies. It is uncertain whether the same applies to chronic Achilles tendinopathy (AT). Objective: To investigate altered central pain mechanisms in chronic AT by assessing conditioned pain modulation (CPM) in recreational athletes with and without chronic AT. Methods: Recreational athletes with chronic AT (ATN) rated their tendinopathy symptoms on the VISA‐A, and short forms of the McGill Pain Questionnaire and the Brief Pain Inventory. The CPM effect was triggered in athletes with tendinopathy (ATN, n = 123) and without tendinopathy (CON, n = 100). The cold pressor test was the conditioning stimulus, and pressure pain was the test stimulus. Results: Participants with tendinopathy had lower pressure pain thresholds before (median (IQR) [ATN: 417 (364 − 516) vs CON 601 (459 − 724), P < .01] and during [ATN: 458 (358 − 550) vs CON 633 (506 − 753), P < .01] cold pressor test. No differences were observed for the CPM effect between the two groups ( P = .49). Conclusion: There was no difference in the CPM effect between athletes with AT and pain‐free controls. Perhaps because tendon pain is a peripheral phenomenon, there are no alterations in descending pain modulation with chronic AT.